Integrating genome-wide and epigenome-wide associations for antipsychotic induced extrapyramidal side effects - Kai Yao; Johan H. Thygesen; Siobhan K. Lock; Antonio F. Pardiñas; Antonia L. Pritchard; Israa Elbashir; Abdullah Lodhi; Zain-Ul-Abideen Ahmad; Michael C. O’Donovan; Michael J. Owen; James T. R. Walters; David St Clair; et al. (Psychopharmacology, 2026)
Rationale Antipsychotic medications are the first-line treatment for schizophrenia. Around 40% of people who are treated with antipsychotics could develop extrapyramidal side-effects (EPSE) including: (1) Dyskinesia, (2) Parkinsonism, (3) Akathisia, and (4) Dystonia. Objectives This study aimed to identify genetic risk factors for EPSE presence following antipsychotic treatment. Methods We conducted Genome-wide association (GWAS) and Epigenome-wide association (EWAS) meta-analyses of EPSE, with subset analyses separating first and second generation antipsychotic (FGA/SGA) exposure. We integrated significant EWAS findings from a between-case design to a comparable GWAS for association enrichment. We investigated whether polygenic risk scores (PRS) for schizophrenia, Parkinson’s disease, and Lewy-body dementia could predict EPSE. Results The primary GWAS top SNP rs2709733 (A/G) ( p = 5.755 × 10 −07 ) mapped to a long intergenic non-protein coding RNA, LINC01162 with consistent effects across all cohorts. Subset analyses with distinct FGA exposure indicated suggestive genes such as NAV2 , NRG3 , LSAMP and SGA exposure indicated SHISA9 and CNBD1 which are relevant for schizophrenia, autism, and epilepsy. In our primary EWAS, the most significant differentially methylated position (DMP) was cg05599348 (3.181 × 10 −07 ), located at chrX:103,174,718 (hg19) mapping to TMSB15B . Comparing EPSE cases to healthy controls, we identified nine DMPs associated with EPSE. The DMP cg12044923 (chr2:241453995, hg19), located within the STK32B gene, showed significant enrichment for EPSE association (permutation p = 0.010). STK32B is relevant to both psychiatric and movement disorders, suggesting potential shared mechanisms. Conclusions Our study sheds new light on the potential biological mechanisms underlying EPSE development in schizophrenia, highlighting the importance of exploring both methylation changes and SNP associations.